Preference, Belief, and Welfare - Hausman, Daniel M.; McPherson, Michael S. (American Economic Review, 2016)
Policy choices depend on general values, such as equality, freedom, justice, and welfare. When economists evaluate policies, they focus on their welfare consequences, and they take welfare to be the satisfaction of preferences. Yet most would allow exceptions when preferences are based on obviously false beliefs. Few, for example, would claim that drinking a fatal poison in the mistaken belief that it was water improves a person's welfare. To deny that drinking poison is welfare-enhancing is only good sense, but it creates serious philosophical tensions for the preference-satisfaction view. For one cannot define welfare as the satisfaction of preferences and then admit that satisfying preferences sometimes makes people worse off. Such clear cases are artificial, but the dependence of preferences on unreliable beliefs is a pervasive feature of social life which makes a preference-based standard of welfare generally problematic. Although many kinds of beliefs influence preferences, we shall focus on judgments concerning the probabilities of risky and uncertain outcomes.1